Geguritan Cokli: Analisis Sosiologi Sastra - Paramita, Ida Bagus Gede (Humanis; Vol 25 No 4 (2021)DO - 10.24843/JH.2021.v25.i04.p09, 2021)
Research on Geguritan cokli uses a sociological analysis. The approach used is a calibative approach. Data collection uses the method of reading, translating and listening to Cokli's Geguritan text. The method of analysis, carried out in a descriptive-qualitative way by using the working stages of the theory of sociology of literature and combined with the theory of structure. The results of the analysis are presented in a systematic and structured manner. The results of this study provide an answer that the existence of a literary work can be a reflection of the state of society at that time, although there are some things that are sometimes no longer relevant to use.